Perbedaan Tingkat Kelelahan Kerja pada Tenaga Kerja Antara Shift Pagi, Shift Sore, dan Shift Malam di Bagian Weaving PT. Iskandar Indah Printing Textile Surakarta - Arifin, Achmad; , Dr. Suwaji, M.Kes; , dr. Hardjanto, M.S., Sp.OK (2013)
PT. Iskandar Indah Printing Textile Surakarta constituting textile's firm raw cloth producer applying system gets innings( shift ). To the effect of observational it is subject to be know the difference job exhaustion zoom among shift morning, shift evening, and night shift at sectioned Weaving PT. Iskandar Indah Printing Textile Surakarta. This research is observational analytic observasional with approaching cross sectional, dianalisis's data statistically and proposional. Employ sample at sectioned Weaving taken by ala purposive is sampling and quota is sampling . Total sample 45 person of populations criterion pock already been established that up the mark which is female energy Age; 25 - 45 years; working life>3 months; job attitude stands up; discipline uses ear shielding tool and has the honour to become sample. This observational variable is work's shift ( shift morning, shift evening, and shift night) and job exhaustion. Gathered data with measure labouring job exhaustion zoom utilizes Reaction Timer L77 Lakassidaya. Analisis who is utilized is statistical quiz non parametrik Kruskal Wallis . analisis menunjukan's result increases job exhaustion among shift morning( 331. 19 + 67. 92), shift evening (386. 35 + 86. 53), and shift night (475. 35 + 103,95) pointing out point that really signifikan which is p = 0,001.